Satisfaction toward Quality of Care and Associated Factors among Patients Admitted to Gambella General Hospital, Gambella Region, Southwest Ethiopia - Natnael Animut; Temesgen Kabeta chala; Waju Beyene Salgedo; Muluneh Getachew Geredew; Bekalu Getachew (Advances in Public Health)
Background. Patient satisfaction, the concept continues to become a crucial and commonly used indicator in the sector of health care delivery for determining the quality of health care services. Satisfaction is a highly desirable outcome of clinical care and may even be an element of health status itself. Therefore, a patient’s expression of satisfaction or dissatisfaction can be considered as a judgement on the quality of care in all of its aspects, whatever its strengths and weakness. Objective. The aim of the study is to determine patient satisfaction on the quality of care and associated factors among patients admitted in Gambella General Hospital, Gambella region, southwest Ethiopia, 2020. Methods. A facility-based cross-sectional study design was conducted, and a consecutive sampling technique was used to recruit 271 study subjects among patients admitted to Gambella General Hospital. All patients who stayed at least for five days and were discharged from inpatient wards were considered for this study. A semistructured questionnaire was used for data collection. Data were entered to Epi-data version 4.6 and exported to SPSS V21 for analysis. Binary logistic regression models were fitted to determine statistically significant associations between dependent and independent variables, and multivariable logistic regression with an AOR with a 95% confidence interval was fitted for candidate variables in binary logistic regression, and statistical significance was declared at pvalue < 0.05. Result. The proportion of net patient satisfaction among the total of 271 respondents was 40.2% (95% CI: 34.36–46.04%). Being government employees (AOR = 0.06, 95% CI: 0.02–0.27), availability signs and direction indicators (AOR = 2.6, 95% CI: 1.18–5.54), provision of adequate information on the treatments (AOR = 2.5, 95% CI: 1.18–5.44), getting provider’s attention (AOR = 3.5, 95% CI: 1.65–7.24), and understanding of specific patient needs and concerns (AOR = 6.04, 95% CI: 2.8–12.88) were found to be significant predicators of patient satisfaction on the quality of care. Conclusion. Less than half of the patients were satisfied with the quality of service delivered in the wards of the hospital. Occupation, signs and directions to follow, getting adequate information about treatment, providers’ attention, and understanding of specific needs and concerns of the patients were the significant factors. Thus, we would recommend that the hospital management should closely work together with health professionals, supportive staff, patients, and other concerned stakeholders to improve admitted patients’ satisfaction with the quality of care. Policymakers advised to develop and institutionalize better interpersonal relations in the health system.